Σχεδιασμός μεταλλικών αντηρίδων προσωρινής αντιστήριξης βαθιάς εκσκαφής - Λεοντάρης, Κωνσταντίνος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Πολιτικών Μηχανικών. Τομέας Δομοστατικής. Εργαστήριο Μεταλλικών Κατασκευών, 2016)
The present diploma thesis deals with the investigation of alternative temporary support systems of deep excavations with the use of steel struts. Two different types of retaining systems are examined, the first including the use of vertical and horizontal cross beams between the struts and the other without. Optimum cross-sections of beams are defined and the main goal is to compare the cross-sections of the same structural elements, which belong to different temporary retaining systems. In the first chapter, an introduction to different types of temporary retaining systems is presented and simultaneously the main requirements for the construction of a safe retaining system are briefly mentioned. Furthermore, emphasis is given to the main goal of the thesis. Finally, the contents of the thesis are briefly described. In the second chapter, the design approach and the selection of the appropriate cross-section type, for each of the temporary retaining systems, are presented. Moreover, the data of the prototype structure are mentioned (dimensions of structural components, support conditions, load combinations etc.). Furthermore, linear and non-linear simulations are introduced and special attention is given to non-linearity, since there is an altitude difference, between the supports of the struts, dictated by pertinent codes as an additional initial imperfection. In the third and fourth chapter, the results of an extensive investigation of each temporary retaining system, by means of linear and non-linear analysis, are presented. Initially the characteristics of the numerical models are given and subsequently linear analyses are carried out. The dimensions of the cross-section of beams are calculated, according to the most unfavorable internal forces based on the results of linear static analysis, according to the regulations of EC3. Non-linear analysis is not necessarily for those structural elements. Moreover, the initial evaluation of the struts cross-section dimensions is calculated based on the unfavorable internal forces mentioned above for both levels of the retaining system. The final evaluation of the struts cross-sections is made employing the most unfavorable axial internal forces, which are introduced as axial design forces in the non-linear analysis. It should be underlined that the evaluation of the cross-section of the struts should take into consideration the altitude difference between the supports of the strut, which is not being taken into account in linear analysis. The construction stages of the temporary retaining system that includes the cross beams between the struts (fourth Chapter) are introduced both to linear and non-linear simulations. In the occasion of the temporary retaining system with single struts, the introduction of construction stages is not needed, as the struts of each level act separately. Furthermore, parametric investigations based on the size of the altitude between the supports of the strut and the size of the initial bow imperfection are examined. The results of the first parametric investigation showed that there is no reduction in the resistance load of the struts, for a realistic range of values of altitude difference the supports of the struts. Concerning the second parametric investigation the main conclusion that arises is that the larger the initial bow imperfection is, the lower the resistance load of the strut is. In the last parametric investigation carried out, the value of the stiffness of friction spring is examined. For values, varying from 5% to 50% of the transverse stiffness of compression soil springs, the cross-section of the beam is adequate. In the fifth chapter, the excavation area is considered to be of finite length and closed on all four sides, while in the above retaining systems, the excavation area was considered to be of infinite length. This more realistic approach showed that the amount of the compressive axial force in the longitudinal beams is rapidly increasing, requiring larger cross sections. The cases of using one or two diagonal struts on each side at the edge of the excavation is examined. In the sixth and final chapter, conclusions of the diploma thesis are presented and a brief summary of the general approach of the current thesis is mentioned.